PELAKSANAAN PENDIDIKAN KEWIRAUSAHAAN DAN PENGARUHNYA BAGI KREATIVITAS MAHASISWA - Fawzan, Ryan; Djafar, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2024)
This research was raised from concerns regarding the lack of entrepreneurship education among students. This research is qualitative in nature with the aim of introducing the implementation of entrepreneurship education and its influence on student creativity. The discussion in this journal is 1. What students gain after studying entrepreneurship, 2. What impact on student creativity after studying entrepreneurship 3. What problems must be faced in introducing entrepreneurship to students. The method used in the research is a descriptive approach, namely focusing on explanations, and is carried out by means of interviews, observational data collection, and questionnaires.